Pengaruh Metode Latihan Dan Media Video Terhadap Kecepatan Reaksi Pemain Bola Voli (The Effect of Training Methods and Video Media on the Reaction Speed of Volleyball Players) - Suryadi Suryadi; Rudy Sumiharsono; Eges Triwahyuni (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The problem in this study is whether there is an effect of training methods and the use of video media together on the reaction speed of youth volleyball athletes in class VII A SMPN 3 Genteng Banyuwangi in the Even Semester of the 2022/2023 Academic Year. X1 variable (practice method) 3 indicators: 1) serve over, 2) smash, 3) block. Variable X2 (use of video media) 3 indicators: 1) top serve, 2) shuttle run, 3) zig zag run. Variable Y (reaction speed) 3 indicators: 1) arm muscle strength, 2) stalk muscle strength, 3) ball drops drill. Causal quantitative research design. The method of determining the purposive sampling area. Population research technique population research. Data collection techniques: 1). observation, 2). interview, 3). document, 4) questionnaire, 5). test. Data analysis 1) instrument test, 2) classic assumption test, 3) hypothesis test. T-test results of the effect of the training method on reaction speed (2.841> 2.004227), t-test of using video media on reaction speed (2.434> 2.004227), F-test results of t-test of training methods and use of video media on reaction speed (3.586> 3,32). So it can be concluded that the training method and video media have an effect on reaction speed so that H0 is rejected.